High Performance Textiles - Elmaaty, Tarek M. Abou; Plutino, Maria Rosaria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
High-performance or hi-tech textiles represent the keystone of the present and the future for all industrial sectors, which require lightening, flexibility, and the high mechanical resistance as well as thermal stability of the materials. As described within this Special Issue, the applications of these advanced systems are innovative and also highly technological: from water-repellent to stain-resistant fabrics, from being flame-resistant to antibacterial/antifouling, from being insulating to conductive, and from environmental protection systems to smart textiles. High-performance textiles also meet all of the actual requirements of sustainability and environmental protection of modern industry.